SGLT2 Inhibitors Play a Salutary Role in Heart Failure via Modulation of the Mitochondrial Function - Maejima, Yasuhiro (Frontiers in Cardiovascular Medicine, 2020)
Three cardiovascular outcome trials of sodium glucose cotransporter 2 (SGLT2) inhibitors, including the EMPA-REG OUTCOME trial, CANVAS Program, and DECLARE TIMI 58 trial, revealed that SGLT2 inhibitors were superior to a matching placebo in reducing cardiovascular events, including mortality and hospitalization for heart failure, in patients with type 2 diabetes. However, the detailed mechanism underlying the beneficial effects that SGLT2 inhibitors exert on cardiovascular diseases remains to be elucidated. We herein review the latest findings of the salutary mechanisms of SGLT2 inhibitors in cardiomyocytes, especially focusing on their mitochondrial function-mediated beneficial effects. The administration of SGLT2 inhibitors leads to the elevation of plasma levels of ketone bodies, which are an efficient energy source in the failing heart, by promoting oxidation of the mitochondrial coenzyme Q couple and enhancing the free energy of cytosolic ATP hydrolysis. SGLT2 inhibitors also promote sodium metabolism-mediated cardioprotective effects. These compounds could reduce the intracellular sodium overload to improve mitochondrial energetics and oxidative defense in the heart through binding with NHE and/or SMIT1. Furthermore, SGLT2 inhibitors could modulate mitochondrial dynamics by regulating the fusion and fission of mitochondria. Together with ongoing large-scale clinical trials to evaluate the efficacy of SGLT2 inhibitors in patients with heart failure, intensive investigations regarding the mechanism through which SGLT2 inhibitors promote the restoration in cases of heart failure would lead to the establishment of these drugs as potent anti-heart failure drugs.